Exploring Vision-Related Quality of Life: A Qualitative Study Comparing Patients’ Experience of Cataract Surgery with a Standard Monofocal IOL and an Enhanced Monofocal IOL - Blancafort Alias S; Del Campo Carrasco Z; Salvador-Miras I; Luna Mariné S; Gómez Prieto MJ; Liñán Martín F; Salvà Casanovas A (Clinical Ophthalmology, 2022)
Sergi Blancafort Alias,1 Zoraida Del Campo Carrasco,2 Ignacio Salvador-Miras,2 Sabina Luna Mariné,2 María José Gómez Prieto,2 Francesca Liñán Martín,2 Antoni Salvà Casanovas1 1Fundació Salut i Envelliment (Health and Ageing Foundation), Universitat Autònoma de Barcelona (UAB), Barcelona, 08041, Spain; 2Service of Ophthalmology, Hospital de Sant Pau, Barcelona, 08025, SpainCorrespondence: Sergi Blancafort Alias, Fundació Salut i Envelliment (Health and Ageing Foundation), Universitat Autònoma de Barcelona (UAB), Sant Antoni Maria Claret, 171, Barcelona, 08041, Spain, Tel +34 93 433 50 30, Email sergi.blancafort@uab.catPurpose: To explore quality of life related with intermediate vision of patients before and after cataract surgery, and to make patients’ experience available for the design of future scales that assess visual function related with intermediate distance.Patients and Methods: A qualitative research methodology based on thematic content analysis was used to explore vision-related quality of life based on the experiences of patients with cataract. Patients were recruited at the Service of Ophthalmology of the Hospital de Sant Pau (Barcelona, Spain). Data were collected through nineteen semi-structured interviews conducted with patients diagnosed with cataract and implanted with a standard aspheric monofocal intraocular lens (IOL) (Tecnis® ZA9003) (n = 6), an enhanced monofocal IOL (Tecnis® Eyhance ICB000) (n = 6), and patients from the waiting list (n = 7). The data analysis consisted in coding, aggregation, and theme development of the transcribed audios.Results: Patients on waiting lists reported difficulty and insecurity in performing daily and meaningful tasks related to near visual ranges (eg: threading a needle, reading price tags), intermediate (eg: using a computer or dialling numbers on a smartphone), and distant (eg: recognizing faces, walking on uneven surfaces). Patients after surgery with the standard IOL reported improvement in performing activities mainly in the distant visual range, but also the need for a better communication with clinical staff to adjust their own expectations on the results of the surgery. Finally, patients implanted with the enhanced IOL reported satisfaction and improved visual function in performing daily activities, especially those related to the intermediate visual range.Conclusion: Our exploratory study found that patients after cataract surgery with the enhanced IOL reported a better performance in activities that require the intermediate vision. These results will inform the development of scales to assess vision-related quality of life in the intermediate visual range prioritizing outcomes according to patients’ daily and meaningful activities.Keywords: quality of life, cataract, qualitative research, intraocular lenses